Improving Student's Ability through Instructional Tasks on Self-Introduction and Describe Favorite Things - Nur Azizah, Eva Aviah; Ratna Dewi, Yaniar; Nurhidayat, Eka (Papanda Journal of English Education, 2024)
English speaking ability is an important skill that is still low among junior high school students in Indonesia, due to lack of practice, motivation, and interesting learning media. This study aims to test the effectiveness of speaking tasks that focus on self-introduction and description of favorite things in improving students' speaking ability. Using quantitative methods with quasi-experimental design, this study involved ten junior high school students selected by purposive sampling. The instrument in this study was a speaking test that measured fluency, vocabulary, grammar, pronunciation, and comprehensibility. Data were analyzed to determine significant changes in students' speaking skills after the intervention. This study shows that self-introduction and description of favorite things-based learning tasks significantly improve junior high school students' English speaking ability. The statistical test results show a significant increase in Posttest scores compared to Pretest (p < 0.001), with an increase in student performance consistency. These findings confirm the effectiveness of the communicative and contextual task approach in developing speaking skills and increasing students' confidence in communicating.